[Rezension von: von Paterson, L.L., & Gregory, I. (2018), Representations of poverty and place]: using geographical text analysis to understand discourse - Berberich, Kristin (International journal of corpus linguistics, 2019)
This article reviews Representations of Poverty and Place: Using Geographical Text Analysis to Understand Discourse